2014
DOI: 10.1111/1750-3841.12593
|View full text |Cite
|
Sign up to set email alerts
|

Emulsifying Properties of Legume Proteins Compared to β‐Lactoglobulin and Tween 20 and the Volatile Release from Oil‐in‐Water Emulsions

Abstract: The emulsifying properties of plant legume protein isolates (soy, pea, and lupin) were compared to a milk whey protein, β-lactoglobulin (β-lg), and a nonionic surfactant (Tween 20). The protein fractional composition was characterized using sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis. The following emulsion properties were measured: particle diameter, shear surface ζ-potential, interfacial tension (IT), and creaming velocity. The effect of protein preheat treatment (90 °C for 10 min) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 41 publications
1
26
0
5
Order By: Relevance
“…Protein aggregation may depend on the protein nature and the physicochemical conditions (pH versus isoelectric point, nature, and concentration of salts, etc.). In any case, it influences the protein solubility [59][60][61]. After 60 min of digestion, the smallest particles initially present in the gastric compartment for PIF and FIF almost totally disappeared and were replaced by larger aggregated particles, which was likely due to acidification [45,62].…”
Section: Gastric Compartmentmentioning
confidence: 99%
“…Protein aggregation may depend on the protein nature and the physicochemical conditions (pH versus isoelectric point, nature, and concentration of salts, etc.). In any case, it influences the protein solubility [59][60][61]. After 60 min of digestion, the smallest particles initially present in the gastric compartment for PIF and FIF almost totally disappeared and were replaced by larger aggregated particles, which was likely due to acidification [45,62].…”
Section: Gastric Compartmentmentioning
confidence: 99%
“…A protein can be used as an emulsifier because of its amphiphilic properties, and plant proteins as well as whey protein are mostly used in this area (Benjamin, Silcock, Beauchamp, Buettner, & Everett, 2015;Cheng, Xiong, & Chen, 2010;Imbart, Regnault, & Bernard, 2016;Negi & Naik, 2017;Xu et al, 2014). A protein stabilizes the O/W emulsion by forming a thin layer at the oil-water interface (Dickinson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, more and more researchers focused on the cheaper sources of proteins with good antioxidant activity and emulsion ability. Many studies have reported that the plant proteins can offer the production of physically stable emulsion like pea, soy, and lupine (Benjamin, Silcock, Beauchamp, Buettner, & Everett, ; Chalamaiah, Jyothirmayi, Diwan, & Dinesh Kumar, ; Embiriekah, Bulatović, Borić, Zarić, & Rakin, ; Rajabzadeh, Pourashouri, Shabanpour, & Alishahi, ). In addition, the protein from animal is another promising possibility applied in the emulsion, which are easily accepted by the consumer for its high nutrition value.…”
Section: Introductionmentioning
confidence: 99%